Analog television in Russia after 2019: Some consequences of the transition to digital tv broadcasting - A.O., Bakhus (2020)
13 years ago, on December 22, 2006, Russian Prime Minister Mikhail Fradkov signed the first government decree regulating the introduction of digital TV in Russia (TASS October 14, 2019). The article summarizes the authors’ long-term research on the country’s transition to digital broadcasting. Historical parallels are drawn with similar events from the history of television development. It is found out how this will affect different segments of the population. Possible ways of realization of digital signal reception for viewers are presented. Two possible ways of distributing terrestrial television content are briefly described. It is concluded that cable operators are monopolists of television broadcasting in apartment buildings.  The results of the study of cable operators in Russia are presented. In contrast to the majority of “winning” headlines in the media the hypothesis that cable TV networks will continue to broadcast in the same format on analog TV sets was confirmed. The authors conclude that the high urbanization of the Russian population has saved most of the country’s viewers from the severe shocks associated with the transition to digital television. A comparison of the television audience of the urban population and suburban residents is given. It points to the problems of pensioners and the poor caused by the digitization of TV.  The problems of possible destruction of the socio-cultural space of Russia due to the reduction or liquidation of local TV companies were highlighted. It is emphasized that it is the rural population that most contributes to the preservation of cultural traditions and moral foundations. It is emphasized that regional and municipal television is the main way of information influence on the local electorate. The analysis of pages of all subjects of the Federation of the official website of the STRC for broadcasting in digital format of local television is carried out. The dynamics of the emergence of new regional stations on the air was indirectly measured.  In conclusion, measures are proposed to unite the population of the country through the programs of regional companies